Gambaran indeks Bolton pada pasien yang dirawat dengan piranti ortodontik lepasan di Rumah Sakit Gigi Mulut Universitas Hasanuddin Overview of Bolton index on patients treated with removable orthodontic appliance in Dental Hospital of Hasanuddin University - Taufiq Demmajannang; Eka Erwansyah (DiscoverSys Inc., 2013)
Orthodontic treatment requires complete planning. Various analyzes is needed to determine the treatment plan; one ofthem is analysis of tooth size differences or Bolton analysis. Orthodontic treatments in Dental Hospital of HasanuddinUniversity do not apply Bolton analysis, so it is necessary to know the overview of Bolton index of the cases that have beentreated. This observational descriptive study was conducted in Department of Orthodontics, Dental Hospital ofHasanuddin University in March-May 2012. The samples were patients who completed treatment in 2010-2011. A total of156 samples consisting of 117 females and 39 males. The result showed that the non-intervention group Ideal AnteriorBolton Ratios and group Overall Bolton Ratio <93.21% have a tendency orthodontic treatment success rate, higher thanthe other groups. While the group Overall Bolton Ratio <89.39% showed the lowest successful rate of orthodontictreatment. The conclusion is the case with interventions of extraction, slicing, and expansion showed inconsistenciestendency of the three categories of orthodontic treatment outcome assessment, namely canine position, overjet, andoverbite.